A study of atmospheric gas concentrations and estimates of dry deposition fluxes at the scale of major African ecosystems - (:unkn) unknown (My University, 2011)
This research, conducted as part of IDAF (IGAC/DEBITS/AFrica*) program, is a contribution to the study of atmospheric constituent deposition on the surface of the earth, in tropical Africa. It concerns the study of atmospheric concentrations of nitrogen gases (ammonia, nitrogen dioxide, nitric acid), sulfur dioxide and ozone, and their dry deposition in West and Central Africa. The gases were measured on a monthly basis by the technique of passive samplers over a ten year period (1998-2007) at seven remote sites within the framework of the IDAF network. The sites are located to represent a transect of African ecosystems, i.e., dry savanna-wet savanna - forest. The validation and the analysis of the decadal IDAF database of " IDAF gases " allowed to establish (1) the levels of surface gaseous concentration characteristic of each major ecosystem and (2) to study their monthly, seasonal, annual and interannual mean variations on the transect of ecosystems. Dry deposition fluxes were estimated by the inferential method based on dry deposition velocities (Vd) calculated using the "big leaf" model of Zhang et al. (2003b). In the model of deposition, surface and meteorological conditions specific to IDAF sites have been adapted and validated in order to simulate Vd representative of major African ecosystems. The monthly, seasonal and annual mean variations of gaseous dry deposition fluxes (NO2, HNO3, NH3, O3, and SO2) are analyzed. A budget of total nitrogen atmospheric deposition (dry + wet) is proposed at the African ecosystem scale. The total nitrogen deposition estimated is around 6-9 kgN.ha-1.yr-1, 7-10 kgN.ha-1.yr-1 and 13 kgN.ha-1.yr-1 respectively in dry savannas, wet savannas and forests, with a relative contribution of dry deposition in the gaseous form to the total nitrogen deposition between 46 and 71% for all ecosystems. We have also established an emission-deposition budget of oxidized and reduced nitrogen compounds for each IDAF station. This b
Keywords: African Research